2010
DOI: 10.1177/0022034510389179
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Hypersensitivity and Oxalates

Abstract: Treatment of dentin hypersensitivity with oxalates is common, but their efficacy remains unclear. Our objective was to systematically review clinical trials reporting an oxalate treatment compared to no treatment or placebo with a dentin hypersensitivity outcome. Risk-of-bias assessment and data extraction were performed independently by two reviewers. Standardized mean differences (SMD) were estimated using random-effects meta-analysis. Of 677 unique citations, 12 studies with high risk-of-bias were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 25 publications
0
72
0
6
Order By: Relevance
“…2 Although current study did not compare Clinpro XT with a placebo control, another recent randomized clinical trial showed that resin-modified GIC was more effective than the placebo in reducing DH for up to 4 weeks. 2,29,31,32,33 Further, a split-mouth study design was adopted to eliminate the effects of individual conceptions of pain, pain perception, oral hygiene habits, dietary habits and psychosomatic factors. 14 Although the ultimate test of any treatment option is how well it works in clinical practice, the randomized, controlled and double-blind clinical trial is the gold standard for determining efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…2 Although current study did not compare Clinpro XT with a placebo control, another recent randomized clinical trial showed that resin-modified GIC was more effective than the placebo in reducing DH for up to 4 weeks. 2,29,31,32,33 Further, a split-mouth study design was adopted to eliminate the effects of individual conceptions of pain, pain perception, oral hygiene habits, dietary habits and psychosomatic factors. 14 Although the ultimate test of any treatment option is how well it works in clinical practice, the randomized, controlled and double-blind clinical trial is the gold standard for determining efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…47,67 However, a meta-analysis of the published papers regarding oxalates found little evidence regarding a positive clinical effect of oxalates. 48 No oxalate-containing toothpaste was tested in the present study. Comparison with the reference toothpaste (positive control).…”
Section: Discussionmentioning
confidence: 99%
“…47 However, a systematic review regarding the effectiveness of oxalates in the treatment of dentine hypersensitivity determined that that single treatments of oxalates had no effect on dentine hypersensitivity compared to placebos. 48 The mechanisms of the action of fluorides in desensitizing dentine hypersensitivity remain unclear. Although most toothpastes contain fluorides in some form, the incidence of dentine hypersensitivity remain high.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, oxalates have been used to precipitate and occlude the tubules. However, a systematic review recently revealed that with the possible exception of 3 % monohydrogen monopotassium oxalate, available evidence does not currently support the recommendation of dentin hypersensitivity treatment with oxalates [15]. …”
Section: Current Management Of Dhsmentioning
confidence: 99%